Follow-up after treatment for head and neck cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Simo, R; Homer, J; Clarke, P; Mackenzie, K; Paleri, V; Pracy, P; Roland, N
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. In the absence of high-level evidence base for follow-up practices, the duration and frequency are often at the discretion of local centres. By reviewing the existing literature and collating experience from varying practices across the UK, this paper provides recommendations on the work up and management of lateral skull base cancer based on the existing evidence base for this rare condition. Recommendations: Patients should be followed up to a minimum of five years with a prolonged follow-up for selected patients. (G) Patients should be followed up at least two monthly in the first two years and three to six monthly in the subsequent years. (G) Patients should be seen in dedicated multidisciplinary head and neck oncology clinics. (G) Patients should be followed up by dedicated multidisciplinary clinical teams. (G) The multidisciplinary follow-up team should include clinical nurse specialists, speech and language therapists, dietitians and other allied health professionals in the role of key workers. (G) Clinical assessment should include adequate clinical examination including fibre-optic rigid or flexible nasopharyngolaryngoscopy. (R) Magnetic resonance imaging and positron emission tomography combined with computed tomography imaging should be used when recurrence is suspected. (R) Narrow band imaging can be used in the follow-up in selected sites. (R) Second primary tumours should be part of rationale of follow-up and therefore adequate screening strategies should be used to detect them. (G) Patients should be educated with regard to the appearance and detection of recurrences. (G) Patients with persistent pain should be investigated to exclude recurrent disease. (R) Patients should be offered support with tobacco and alcohol cessation services. (R)